Ouregidione from Goniothalamus velutinus (Annonaccae) - Chuah, C. H. ’; C.L. Eel, G.; Goh, S.H. (Malaysian Journal of Science, 1999)
. The structures of ouregidione, aristolactam B(11), goniothalenol, goniothalamin and annonacin, chemicals that were isolated from the stem-bark of Goniothalamus velutinus, were established by NMR spectroscopy. The five compounds were evaluated for their larvicidal activity against Aedes aegypti.